Selected urticaria patients benefit from a referral to tertiary care centres – results of an expert survey. (17th December 2011) - Weller, K.; Schoepke, N.; Krause, K.; Ardelean, E.; Bräutigam, M.; Maurer, M.
Abstract Background Urticaria is a frequent reason for consultations. Recently, it has been demonstrated that the management of chronic spontaneous urticaria (csU) in the practice setting does not fully comply with published guidelines. In addition, it was shown that one of four csU patients is referred to specialized centres. Objective To analyse the management of urticaria patients in tertiary referral centres. Methods During a standardized expert‐to‐expert interview, 41 specialists from German tertiary care centres were asked for different aspects of urticaria patient care with a special focus on csU. Results On average, the participating centres saw 25 csU patients per month. All ran programmes for the identification of underlying causes with an average success rate of 45 ± 3% which is considerably higher as has been found in the practice setting. In those patients where an identification succeeds, infections, drugs, intolerance and autoreactivity were reported to be causes in 41%, 20%, 17% and 16%. In their symptomatic treatment the majority of centres (71%) followed the guidelines by using regular dosed non‐sedating H1‐antihistamines as first line and higher doses (61%) as second line option. In contrast to the practice setting, meaningful experience also existed for alternative therapies in antihistamine‐resistant patients, such as dapsone, cyclosporin and omalizumab. The expenditure of time, laboratory costs and frequency of follow‐up visits was reported to be above average in case of csU. Conclusion This study indicates that some urticaria patients, especially those with unknown causes or with an H1‐antihistamine‐resistant disease, may benefit from a referral to tertiary care centres.